2008
DOI: 10.1111/j.1753-318x.2008.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Using satellite‐based rainfall estimates for streamflow modelling: Bagmati Basin

Abstract: In this study, we have described a hydrologic modelling system that uses satellite‐based rainfall estimates and weather forecast data for the Bagmati River Basin of Nepal. The hydrologic model described is the US Geological Survey (USGS) Geospatial Stream Flow Model (GeoSFM). The GeoSFM is a spatially semidistributed, physically based hydrologic model. We have used the GeoSFM to estimate the streamflow of the Bagmati Basin at Pandhera Dovan hydrometric station. To determine the hydrologic connectivity, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 13 publications
4
52
0
Order By: Relevance
“…Yatagai and Kawamoto [18] found that the TRMM Precipitation Radar (PR) product underestimated summer precipitation by 28-38% over the Himalayas. Focusing specifically on Nepal, Shrestha et al [19] found that streamflow in the Bagmati river (in a region of Nepal with relatively dense station coverage) was simulated poorly when forced by basin-wide precipitation from a Climate Prediction Center (CPC) satellite-derived product compared to using interpolated rain gauge measurements, since the CPC product failed to capture some of the heaviest precipitation events. Similarly, Islam et al [20] found that Version 6 of the TRMM product generally underestimated daily precipitation over Nepal compared to available station data.…”
Section: Introductionmentioning
confidence: 99%
“…Yatagai and Kawamoto [18] found that the TRMM Precipitation Radar (PR) product underestimated summer precipitation by 28-38% over the Himalayas. Focusing specifically on Nepal, Shrestha et al [19] found that streamflow in the Bagmati river (in a region of Nepal with relatively dense station coverage) was simulated poorly when forced by basin-wide precipitation from a Climate Prediction Center (CPC) satellite-derived product compared to using interpolated rain gauge measurements, since the CPC product failed to capture some of the heaviest precipitation events. Similarly, Islam et al [20] found that Version 6 of the TRMM product generally underestimated daily precipitation over Nepal compared to available station data.…”
Section: Introductionmentioning
confidence: 99%
“…Several precipitation estimates derived from satellite data or modeled through retrospective weather forecast model analysis (reanalysis) provide estimates that are independent from gauge networks. Both types of precipitation estimates have being increasingly used in hydrological applications [e.g., for reanalysis (Dedong et al 2007;Li et al 2009;Yan et al 2010;MiguezMacho and Fan 2012) and for satellite (Shrestha et al 2008;Behrangi et al 2011;Khan et al 2012; among many others)].…”
Section: Introductionmentioning
confidence: 99%
“…For the preparedness phases, establishing an early warning system is the most recognized application of EO. Applications for early flood and drought warnings were proposed [20,21,[27][28][29] and have been introduced as pilot operations [45].…”
Section: Earth Observationmentioning
confidence: 99%
“…Earth observations (EO) have served as an important information resource in DRM and has been applied to earthquakes [13][14][15], tsunami arrival predictions [16], volcanic hazards [17,18], floods [19][20][21][22][23], landslides [24,25], forest fires [26], and drought monitoring and prediction [27][28][29][30][31]. Earth observations can help to simultaneously capture the land condition of a broad area and are less expensive than field surveys.…”
Section: Earth Observationmentioning
confidence: 99%